Practitioner Perceptions of the Assessment and Diagnosis of Autism in Australia. (30th June 2016) - Ward, Samantha L.; Sullivan, Karen A.; Gilmore, Linda
Abstract : Objective: Autism Spectrum Disorder (ASD) can potentially be diagnosed by 3 years of age. Yet, 2012 Australian diagnostic data showed most children are diagnosed after this age. This study examined whether an ASD diagnostic "gap" exists and explored practitioners' perceptions of the assessment and diagnostic process. Method: Using a modified version of an existing questionnaire, we undertook a national survey of Australian practitioners who assess infants and children with possible ASD (psychologists, n =54; paediatricians, n =42; psychiatrists, n =8). Results: Approximately 63% of practitioners reported most likely recommending an ASD diagnosis in a child 3 years or older. Over 60% of practitioners identified the following factors as influencing their practice in relation to ASD diagnosis in children under 3 years of age: preference for a "watch and wait approach" (92%); the perceived difficulty of the diagnosis (79%); inability to see children early enough because of initial assessment waiting list (75%), and the perceived limitations of diagnostic aids, including assessment measures (63%) and the diagnostic criteria (69%). Variations in assessment and diagnostic practices were reported by the three professional groups. Conclusion: A number of factors may influence the timing of ASD diagnosis for children in Australia and could contribute to a diagnostic "gap." The practitioner‐reported challenges suggest potential improvements to the ASD diagnosis process.